The Oxford Handbook of Thinking and Reasoning 2012
DOI: 10.1093/oxfordhb/9780199734689.013.0024
|View full text |Cite
|
Sign up to set email alerts
|

Insight

Abstract: In the century since the Gestalt psychologists introduced insight as a component process of perception and problem solving, researchers have studied the phenomenological, behavioral, and neural components of insight. Whether and how insight is different from other types of problem solving, such as analysis, has been a topic of considerable interest and some contention. In this chapter we develop a working definition of insight and detail the history of insight research by focusing on questions about the influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 79 publications
0
24
0
2
Order By: Relevance
“…van Steenburgh et al. () have speculated that this effect of positive affect may be due to the ability of positive affect to encourage a broadening of attention (see also Rowe, Hirsch, & Anderson, ). A broad attentional focus has long been known to be associated with creative behavior (e.g., Ansburg & Hill, ; Mendelsohn & Griswold, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…van Steenburgh et al. () have speculated that this effect of positive affect may be due to the ability of positive affect to encourage a broadening of attention (see also Rowe, Hirsch, & Anderson, ). A broad attentional focus has long been known to be associated with creative behavior (e.g., Ansburg & Hill, ; Mendelsohn & Griswold, ).…”
Section: Discussionmentioning
confidence: 99%
“…People frequently describe solving problems with either an analytic, step‐by‐step process (Morrison, ), or a comparatively unconscious process resulting in unexpected answers (van Steenburgh, Fleck, Beeman, & Kounios, ). In the latter situation people show little ability to predict their sudden insight (Metcalfe, ), yet have great confidence in the solution that seemingly came from unconscious processing (Simonton, ; Smith & Ward, ).…”
Section: Incubation During Insight Problem‐solvingmentioning
confidence: 99%
“…Drawing upon the previous study ( Karwowski et al, 2020 ), which demonstrated that even brief information about coronavirus elevates people’s anxiety, we predicted that making coronavirus salient will negatively influence the efficiency in solving tasks that require creative insight yet will not harm analytical thinking. In this study, we operationalized creativity as insight tasks: misleading problems that require restructuring of the problem representation and viewing it from a different angle in order to achieve the solution ( Jason van Steenburgh, Fleck, Beeman, & Kounios, 2012 ). As such, they engage flexible and global thinking mode ( Baas et al, 2011 ).…”
Section: The Present Studymentioning
confidence: 99%
“…Las negociaciones son definidas como un proceso en el que intervienen dos o más partes, que son sometidas a ofrecer y recibir beneficios a través de una transacción, cuya finalidad radica en resolver un conflicto de intereses o tener un acuerdo de negocio entre las partes involucradas (Brett, 2017;Van Steenburgh, Fleck, Beeman, & Kounios, 2012). De acuerdo con Walton y McKersie (1965), se han identificado dos tipos de estrategias de negociación: negociación integrativa y negociación distributiva.…”
Section: Negociaciónunclassified